Directions and Practices for Implementing Early Care for Children with Developmental Disabilities in the Ukrainian and Swedish ECEC Systems - Tarasun, Valentyna; Melnyk, Nataliia; Stepanova, Tetiana; Dotsevych, Tamiliia; Al-Mrayat, Olena (Journal of Intellectual Disability - Diagnosis and Treatment, 2024)
Background: This article explores the strategies and approaches used in Ukraine and Sweden's Early Childhood Education and Care (ECEC) systems for providing early care to children with developmental disabilities. It examines the similarities and differences in policies, legislation, professional training, family involvement, resource allocation, service provision, integration vs. segregation practices, and cultural attitudes toward disability between the two countries. Methods: This study used questionnaires and surveys, analysis of learning outcomes, performance evaluation, and an expert evaluation method. Results: The authors analyze Ukrainian best practices for implementing early care for children with developmental disabilities. In the example of the Swedish system and the context of a comparative investigation of early care for children with developmental disabilities in the countries under analysis, the authors pointed out the strengths and weaknesses of both systems and distinguished the similarities and differences. The theoretical study allowed the practical perspectives and critical Swedish practices that could be implemented in modern Ukrainian practices, among which the most relevant perspectives are those related to early intervention programs, individualized support plans, and fostering partnerships with community organizations and healthcare providers. Research Limitation: The experimental part of the study included a relatively small sample size (50 respondents) and was characterized by a short duration (three months). This may limit the ability to generalize the results. Conclusions: Additionally, the emphasis on inclusive curriculum and environments, as well as professional development opportunities for educators on inclusive practices, could significantly enhance modern Ukrainian practices in early care for children with developmental disabilities.